Developing Database System for Managing Medical Insurance Claims in the Human Resource Department - Salma Eka Ramadhany; Hery Hamdi Azwir (Industrial Engineering, Faculty of Engineering, Universitas Sebelas Maret, 2020)
PT. X Indonesia provides medical insurance for their employee from BPJS Kesehatan and other private company insurance. Currently, the data management of medical insurance members is not efficient and effective because the data regarding medical insurance are managed manually using MS Excel. The manual process leads to incorrect data input and causes a delay in the process of getting treatment and reimbursement claim process. The company will reimburse the payment but the process is long and complicated because the company should check the limitation for reimbursement claim per year. To solve the problem, database systems are constructed using System Development Life Cycle (SDLC) methodology which consists of five phases; systems planning, systems analysis, systems design, systems implementation, and system test, and deployment. The business process flow diagram of the current and proposed system is analyzed. After that, user requirements are determined. The data flow diagram and entity-relationship diagram (ERD) is constructed. And the system is developed using MS Access. Finally, the system is deployed. The result is an application running in MS Access that can manage medical insurance claim with more efficient and effective, compare to previous MS Excel.